2020
DOI: 10.32598/hms.26.3.1871.7
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effect of Massage With Lavender Gel and Piroxicam Gel on Exercise-induced Muscle Soreness in Male Students of Gonabad University of Medical Sciences

Abstract: Aims: Muscular pain is a common complication of physical activity. The purpose of this study was to compare the effect of massage with lavender gel and piroxicam gel on exercise-induced muscle pain in male students of Gonabad University of Medical Sciences. Methods & Materials: This semi-experimental study was performed on 75 male students of Gonabad University of Medical Sciences in 2018. The Samples were randomly divided into three groups of 25, including a lavender gel massage group, a piroxicam gel mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…In another study, the DOMS was reduced after 24 hours of effleurage massage post-eccentric exercise (14). In Mottaghy et al, pain and soreness lowered after massage (15). Hajizadeh-Jabdargh et al found that CK, fatigue, and pain following kick exercise increased, but the level of CK decreased two hours after exercise in the massage group (16).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the DOMS was reduced after 24 hours of effleurage massage post-eccentric exercise (14). In Mottaghy et al, pain and soreness lowered after massage (15). Hajizadeh-Jabdargh et al found that CK, fatigue, and pain following kick exercise increased, but the level of CK decreased two hours after exercise in the massage group (16).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that lavender oil, which is applied through massage, is rapidly absorbed starting from the epidermis layer of the skin and participates in the circulation, and it is thought that it provides relaxation and changes the perception of pain by increasing the parasympathetic activity with the effect of active ingredients and stimulating the sense of touch 27,28 . In the literature, it has been reported that the group that was massaged with lavender gel after exercise reduced muscle pain more 28 . It has also been reported that lavender oil has anti-inflammatory and analgesic effects [29][30][31] .…”
Section: Introductionmentioning
confidence: 99%